Rational Design, Synthesis, and Biological Evaluation of Third Generation α-Noscapine Analogues as Potent Tubulin Binding Anti-Cancer Agents - Manchukonda, Naresh Kumar; Naik, Pradeep Kumar; Santoshi, Seneha; Lopus, Manu; Joseph, Silja; Sridhar, Balasubramanian; Kantevari, Srinivas (PLOS ONE, 2013)
Systematic screening based on structural similarity of drugs such as colchicine and podophyllotoxin led to identification of noscapine, a microtubule-targeted agent that attenuates the dynamic instability of microtubules without affecting the total polymer mass of microtubules. We report a new generation of noscapine derivatives as potential tubulin binding anti-cancer agents. Molecular modeling experiments of these derivatives 5a, 6a-j yielded better docking score (-7.252 to -5.402 kCal/mol) than the parent compound, noscapine (-5.505 kCal/mol) and its existing derivatives (-5.563 to -6.412 kCal/mol). Free energy (ΔGbind) calculations based on the linear interaction energy (LIE) empirical equation utilizing Surface Generalized Born (SGB) continuum solvent model predicted the tubulin-binding affinities for the derivatives 5a, 6a-j (ranging from -4.923 to -6.189 kCal/mol). Compound 6f showed highest binding affinity to tubulin (-6.189 kCal/mol). The experimental evaluation of these compounds corroborated with theoretical studies. N-(3-brormobenzyl) noscapine (6f) binds tubulin with highest binding affinity (KD, 38 ± 4.0 µM), which is 4.0 times higher than that of the parent compound, noscapine (KD, 144 ± 1.0 µM) and is also more potent than that of the first generation clinical candidate EM011, 9-bromonoscapine (KD, 54 ± 9.1 µM). All these compounds exhibited substantial cytotoxicity toward cancer cells, with IC50 values ranging from 6.7 µM to 72.9 µM; compound 6f showed prominent anti-cancer efficacy with IC50 values ranging from 6.7 µM to 26.9 µM in cancer cells of different tissues of origin. These compounds perturbed DNA synthesis, delayed the cell cycle progression at G2/M phase, and induced apoptotic cell death in cancer cells. Collectively, the study reported here identified potent, third generation noscapinoids as new anti-cancer agents.